2017
DOI: 10.1371/journal.pone.0188167
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative risk factors for postoperative pneumonia after major oral cancer surgery: A retrospective analysis of 331 cases

Abstract: ObjectivePostoperative pneumonia (POP) is common and results in prolonged hospital stays, higher costs, increased morbidity and mortality. However, data on the incidence and risk factors of POP after oral and maxillofacial surgery are rare. This study aims to identify perioperative risk factors for POP after major oral cancer (OC) surgery.MethodsPerioperative data and patient records of 331 consecutive subjects were analyzed in the period of April 2014 to March 2016. We individually traced each OC patient for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 33 publications
4
33
0
Order By: Relevance
“…Our finding was in accordance with the previous randomized controlled clinical studies by Rui patients undergoing oral cancer surgery with tracheotomy 6 and the retrospective analysis of 331 cases after oral and maxillofacial surgery with or without free flap construction in 2017 22 . Previous studies had showed that multiple variables including advanced age, male sex, poor underlying medical condition, surgery location, a higher American Society of Anesthesiologists (ASA) grade, tracheotomy and reintubation were associated with an increased risk of postoperative pneumonia 22 .…”
Section: Discussionsupporting
confidence: 92%
“…Our finding was in accordance with the previous randomized controlled clinical studies by Rui patients undergoing oral cancer surgery with tracheotomy 6 and the retrospective analysis of 331 cases after oral and maxillofacial surgery with or without free flap construction in 2017 22 . Previous studies had showed that multiple variables including advanced age, male sex, poor underlying medical condition, surgery location, a higher American Society of Anesthesiologists (ASA) grade, tracheotomy and reintubation were associated with an increased risk of postoperative pneumonia 22 .…”
Section: Discussionsupporting
confidence: 92%
“…3,28 Most of our patients were male (70.7% vs. 69.6%, respectively), of advanced age (mean age: 59 years vs 61 years), required a prolonged operation (340 min vs 327 min), and underwent tracheotomy (53.5% vs 56.9%), which could have been responsible for the high incidence of POP. 30,31 In addition, the time between surgery and the appearance of the first PPCs was 3 (2 to 4) days, which was in agreement with the results of previous large retrospective studies. 32 Our results showed a significant difference in intraoperative opioid consumption between the two groups, and it could be argued that the lower opioid consumption in the sevoflurane group is caused by the analgesic effect of sevoflurane, 33,34 and intraoperative opioid savings are thought to play a role in lower rates of PPCs development.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, our survey revealed the most common PPCs was respiratory infection, registering 14(17.5%) patient in DEX group in comparison with 19 (23.8%) in placebo group. Occurrence of postoperative respiratory infection was the same with the retrospective study in 2015 about 482 patients undergoing oral cancer surgery with tracheotomy 6 and the retrospective analysis of 331 cases after oral and maxillofacial surgery with or without free flap construction in 2017 22 . Previous studies had showed that multiple variables including advanced age, male sex, poor underlying medical condition, surgery location, a higher American Society of Anesthesiologists (ASA) grade, tracheotomy and reintubation were associated with an increased risk of postoperative pneumonia 22 .…”
Section: Discussionmentioning
confidence: 60%
“…Occurrence of postoperative respiratory infection was the same with the retrospective study in 2015 about 482 patients undergoing oral cancer surgery with tracheotomy 6 and the retrospective analysis of 331 cases after oral and maxillofacial surgery with or without free flap construction in 2017 22 . Previous studies had showed that multiple variables including advanced age, male sex, poor underlying medical condition, surgery location, a higher American Society of Anesthesiologists (ASA) grade, tracheotomy and reintubation were associated with an increased risk of postoperative pneumonia 22 . All our patients were older than 51 years and underwent tracheotomy, and most of our patients were male (63.8% vs. 36.3%, 66.3% vs. 33.8%, respectively), which could have been responsible for the high incidence of postoperative pneumonia in our study.…”
Section: Discussionmentioning
confidence: 60%